Collaboration between social science data archives and scientific journals in the development and implementation of data sharing policies (PUBMET, 2022)
Major commercial scientific journal publishers have already introduced data sharing and citation policies, while independent journals are implementing such changes more slowly. As more and more funders of scientific research require researchers to make their research data as open as possible, all journals will have to adapt to support new ways of scientific communication. Social science data archives in Europe and around the world were established decades ago and have collectively accumulated vast experience in dealing with data, especially data that are sometimes hard to share because of various ethical and legal concerns. Because of this knowledge, they also have a role to play in supporting journal editors and publishers in developing and implementing editorial policies related to data sharing and citation.In this short talk we will present examples of support activities for journals from the Slovenian and Croatian Social Science Data Archive (ADP and CROSSDA, respectively). Both are service providers (SPs) for CESSDA ERIC, a recognised European research infrastructure (RIs) for social sciences.As a coordinator of the project establishing Research Data Alliance (RDA) Node in Slovenia, ADP prepared guidelines for Slovenian journals on implementing editorial policies related to data sharing and data citation (Štebe, Bezjak, Dolinar, 2020). These guidelines are based on internationally renowned practices and policies, particularly the RDA Research Data Policy Framework (Hrynaszkiewicz, I., at. al., 2020) and were adopted by four journals (from fields of archaeology, history, linguistics and social sciences) in a pilot phase (Štebe, Dolinar, Bezjak, Inkret, 2020).Both ADP and CROSSDA are part of the ongoing CESSDA Journals Outreach project, which started in 2020. As part of the project, editors-in-chief of several social science journals were invited to share their views on data sharing and to discuss how data archives can provide support. At the same time, CESSDA SPs answered to a survey whose aim was to explore the capacities of data archives to support journals. In 2021, two events were organised for researchers, journal publishers, and data archives to discuss transparency in social science research and the challenges of sharing data through publications.By now, ADP has helped three Slovenian journals to implement research data policies: Socialno delo, Central European Public Administration Review, and Economic and Business Review. These policies are not mandatory, and so far, no author decided to share their data before publishing the article. The journal Javnost, in turn, has taken a different approach. The guest editor of one supplement issue asked the authors who had passed peer review to share and cite their data before publishing with the support of ADP. All authors agreed to make additional effort and prepare the data, documentation, and metadata, so that their results could be verified, and data reused.In Croatia, one journal, Croatian Sociological Review, introduced its first open science policy, which is partly based on the TOP Guidelines (Nosek at al., 2021) and includes several elements of research transparency, not just data transparency (Vučković Juroš, 2021). Data sharing will not be mandatory, and transparency will be implemented taking into consideration various epistemological assumptions in the humanities and social sciences. The next step is to set up instructions for authors and reviewers to make this policy official, which will be done in cooperation with CROSSDA.
Keywords: data citation; data sharing; editorial policies; scientific journals; social science data archives